Book Review: Atul Joshi, Winning a Billion Consumers: A Disruptive Approach for Success in India. (August 2016) - Tandon, Neelam
Atul Joshi, Winning a Billion Consumers: A Disruptive Approach for Success in India . New Delhi: SAGE Publications India Pvt Ltd, 2016, 261 pp., ₹450 (ISBN: 978-93-515-0557-0)